Sampling of plant in coffee for evaluation of nutritional status - Cintra, Antonio Carlos de Oliveira; Rozane, Danilo Eduardo; Natale, William; Silva, Silvia Helena Modenese Gorla da; Barbosa, José Carlos; Lopes, Marcelo Domingos Chamma (Coffee Science - ISSN 1984-3909, 2015)
The foliar fertilization assists programs in order to obtain higher yields, however, it is essential to know the ideal number of plants to be sampled. The study aimed to determine in commercial coffee plantations, subjected to two water regimes, the number of plants to be sampled and estimate the sample error for the diagnosis of nutritional status of that culture. The work consisted of two studies where samples of leaves were collected in rainfed and irrigated farming. For both studies the completely randomized design, with four treatments and five repetitions that consisted of leaf collection in 5, 10, 20 and 40 coffee plants per sampling unit was used. So to keep the sampling error below 10 % for the macronutrient, leaf sampling five composite samples at 10 and 20 plants per sampling unit under irrigated and rainfed conditions, respectively, is sufficient. As for the content of micronutrients collecting 20 plants in systems except Cu and Mn requiring higher sampling five composite samples of 40 plants in rainfed systems are needed.